Types, Forms, and Functions of Code Mixing in the Goyang Jember Program - Santuso; Agus Sariono; Agustina Dewi Setyari (LADU: Journal of Languages and Education, 2023)
Background: The broadcasters and callers in the Goyang Jember program on Prosalina FM radio are a reflection of the Pandalungan community, so the language used is unique and interesting to study. Purpose: This research aims to describe the types, forms, and functions of code mixing in the conversations between broadcasters and callers in the Goyang Jember program on Prosalina FM radio. Design and methods: This research is a qualitative descriptive study. Data collection was carried out using the observation method with tapping, free observation, and note-taking techniques. The data analysis stage used the translational and referential equivalence method with descriptive, identification, and classification techniques. Results: The results of this study found two types of code mixing, namely internal code mixing from Javanese, Madurese, and Osing languages, and external code mixing from Arabic and English languages. The forms of code mixing found were insertion of words (152 data), phrases (42 data), repetition of words (1 data), clauses (24 data), and blasters (5 data). The functions of code mixing found were to build a relaxed and friendly atmosphere, show the ethnic identity of the speaker, show respect to the interlocutor, create humor, and show prestige. The result of this research is expected to provide awareness that code mixing in bilingual or multilingual communities serves to eliminate differences between societal groups and build interpersonal relationships among them.